CoMFA, CoMSIA, HQSAR and Molecular Docking Analysis of Ionone-based Chalcone Derivatives as Antiprostate Cancer Activity - Sharma, R. (Indian J Pharm Sci, 2016)
Androgen receptor has been proved to be effective site for treatment of prostate cancer. Molecular modeling methods performed on forty-three ionone based chalcones derivatives as anti-prostate cancer activity. The designed comparative molecular field analysis, comparative similarity indices analysis and hologram quantitative structure activity relationship models produced statistically significant results with the cross-validated correlation coefficients (q(2)) of 0.527, 0.550 and 0.670, non-cross-validated correlation coefficients (r(2)) 0.636, 0.671 and 0.746 and predicted r(2) (Pred r(2)) of 0.621, 0.563 and 0.732, respectively. Furthermore, bioactive conformation was explored and explained by docking of the potent compound 25 into the binding site of androgen receptor. Present study deals with comparative molecular field analysis, comparative similarity indices analysis and hologram quantitative structure activity relationship and molecular docking studies of the ionone-based chalcones and their derivatives, obtained from literature. The model obtained could be effectively used as a channeling tool for further structure modification and designing of some novel potent anti-prostate cancer compounds.